Math, asked by rohangadge770, 1 year ago

Prove that sec square theta + cot square (90-theta) =2 cosec square (90-theta) -1 ???

Answers

Answered by adityakumar4849
26
HEYYA HERE IS YOUR ANSWER..........._______^^
TAKING L.H.S.
sec^2theetha + cot ^2(90-theetha)
sec^2theetha+ tan^2theetha
sec^2theetha + sec^2thhetha -1
2 sec^2theetha- 1....
NOW R.H.S
2cose^2(90-theetha)-1
2 sec^2theetha-1 ..
HENCE ,
LHS =RHS PROVED....

♡♡♡♡♡♡♡♡♡♡♡♡♡♡♡♡♡
HOPE THIS WILL HELP YOU...

Answered by harendrachoubay
5

\sec^2 \theta+\cot^2 (90-\theta)=2\csc^2 (90-\theta) -1, proved.

Step-by-step explanation:

Prove that, \sec^2 \theta+\cot^2 (90-\theta)=2\csc^2 (90-\theta) -1.

L.H.S.=\sec^2 \theta+\cot^2 (90-\theta)

=\sec^2 \theta+\tan^2 \theta

Using the trigonometric identity,

\tan \theta = \cot (90-\theta)

=\sec^2 \theta+\sec^2 \theta-1

Using the trigonometric identity,

\tan^2 \theta=\sec^2 \theta-1

=2\sec^2 \theta-1

R.H.S.=2\csc^2 (90-\theta) -1

=2\sec^2 \theta -1

∴ L.H.S. = R.H.S.=2\sec^2 \theta -1

Hence, \sec^2 \theta+\cot^2 (90-\theta)=2\csc^2 (90-\theta) -1, proved.

Similar questions